Comparative Wood Anatomy Study of Eight Species of Genus Dipterocarpus - Gupta, Prachi; Gupta, Sangeeta (Indian Forester, 2018)
Comparative wood anatomy of eight species of Dipterocarpus revealed the occurrence of axial canals in short tangential bands surrounded by confluent to aliform axial parenchyma. These speices showed similar qualitative wood anatomical features. However, Coffecient of Variation revealed high level of variability in quantitative wood anatomical features which can be attributed to different environmental conditions from where different samples belong.